Avaliação de dose ocupacional e parâmetros técnicos em seriografias de esôfago, estômago e duodeno pediátricas - Nunes, Gracielly Soares (2020)
Studies of pediatric upper gastrointestinal series performed by fluoroscopy usually require professionals to remain within the examination room to positioning and immobilizing the patient. Knowing and reducing radiation exposure of these individuals is a constantly reported concern. Thus, the present study aimed to estimate the effective dose received by the team involved in pediatric Esophagus, Stomach e Duodenum Seriography. Dose rates and cumulative doses were measured using a parallel plate ionization chamber (Radcal Corporation, model 10X5-6, with a sensitive volume of 180 cm³), for each of the five examination steps. To simulate the occupationally exposed individual and the pediatric patient, two polyethylene dummies filled with water were used. Were also evaluated some technical parameters that influence dose distributions, such as collimation, isocenter distance, lead apron and additional filtration. The results were compared with the literature and with limits set by international standards. The estimate showed values slightly lower, but comparable, to typical medical doses of chest X-rays. The annual effective dose is capable of exceeding the International Commission on Radiological Protection threshold if expanded to hundreds of procedures. For different exam positions, the difference in dose rate is up to 14% and doses in radiography differ by a factor of up to 3.4. The contribution of radiographic images in the total dose may reach 30%, which emphasizes the importance of the last image hold for occupational exposure. The automatic brightness control increases the dose rate to compensate for collimator close. Regarding the variable distance, the dose rate follows the inverse square law, with an accuracy of better than 1%. For tube voltage of 83 kVp, the lead apron decreases the scattered radiation dose rate similar to 49 keV monochrome radiation. The additional filtration suggested by the European Communities reduces the dose rate by tens of percent. Thus, the optimization and standardization of technical parameters, following international recommendations, are sufficient to guarantee diagnostic quality and to reduce occupational exposures.